2011
DOI: 10.1177/1934578x1100600942
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Effects of Nectandra angustifolia Extracts against Bothrops neuwiedi Snake Venom

Abstract: Leaves extracts and essential oil of Nectandra angustifolia were explored for the first time for neutralization of Bothrops neuwiedi diporus snake venom. The ethanol extract was the most active and inhibited both venom activities (hemolytic and coagulant), while the oil was only active on the coagulant activity. These observations confirmed that certain medicinal plants from Corrientes and Chaco Provinces possess significant snake venom neutralizing capacity and need further examination for their active consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…There are few reports in the literature on the antiophidian properties of essential oils. The inhibitory effect of extracts and essential oils from Nectandra angustifolia leaves on the hemolysis and coagulation induced by B. neuwiedi venom were evaluated, showing that the essential oil was only effective in inhibiting coagulation [ 18 ]. The monoterpenes α-pinene, β-pinene and limonene were the major constituents identified in the essential oils evaluated and were considered by these authors as possible coagulation inhibitors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few reports in the literature on the antiophidian properties of essential oils. The inhibitory effect of extracts and essential oils from Nectandra angustifolia leaves on the hemolysis and coagulation induced by B. neuwiedi venom were evaluated, showing that the essential oil was only effective in inhibiting coagulation [ 18 ]. The monoterpenes α-pinene, β-pinene and limonene were the major constituents identified in the essential oils evaluated and were considered by these authors as possible coagulation inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Fibrinogen, a dimeric plasma glycoprotein of 340 kDa composed of six polypeptide chains (α, β, γ), participates in the coagulation cascade, and is converted by thrombin to fibrin monomers [ 37 ]. This protein has been extensively used for the evaluation of the potential fibrinogenolytic effects of snake venoms, and for the verification of potential antiophidian properties of natural compounds, mainly of plant origin [ 3 , 13 , 15 - 18 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants' secondary metabolites possess the ability to neutralize a range of enzymes present in snake venom such as 5 ′ -nucleotidases, protease, phospholipase A 2 , L-amino acid oxidase, and hyaluronidase. Various bioactive compounds have been reported in literature for their ability to inhibit one or more snake venom enzymes, for example, resveratrol [60,61], β-sitosterol [62][63][64], pentagalloyl glucopyranose [31,65], gallic acid [66,67], solanidane [68], alternamin [69], macrolobins A and B [70], and 8-methoxy coumestrol [71]. In this study, phytochemical screening of active fractions of plants' extracts showed the presence of various bioactive compounds such as flavonoids, phenols, saponins, tannins, terpenoids, steroids, and alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrinogenolytic assay allows evaluating the action of proteases and their inhibitors on the proteolysis of fibrinogen molecules. Proteases present in the venoms from Bothrops genus generally induces a proteolytic action on α-chains of fibrinogen molecules, not being very effective in degrading β-chains and without action on γ-chain (Silva et al, 2012;Torres et al, 2012).…”
Section: Discussionmentioning
confidence: 99%